2015
DOI: 10.1039/c5nr03145a
|View full text |Cite
|
Sign up to set email alerts
|

Mapping viscoelastic properties of healthy and pathological red blood cells at the nanoscale level

Abstract: In order to pass through the microcirculation, red blood cells (RBCs) need to undergo extensive deformations and to recover the original shape. This extreme deformability is altered by various pathological conditions. On the other hand, an altered RBC deformability can have major effects on blood flow and can lead to pathological implications. The study of the viscoelastic response of red blood cells to mechanical stimuli is crucial to fully understand deformability changes under pathological conditions. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 41 publications
6
71
1
Order By: Relevance
“…This makes standard experimental probes probing the average structure inadequate for the visualization of this heterogeneity, requiring highly spatially resolved probes. Biological tissues are typically intrinsically heterogeneous; indeed, nowadays new features and properties have been visualized using scanning methods with high spatial resolutions, such as by Atomic Force Microscopy [38][39][40], Confocal Microscopy [40], Scanning Electron Microscopy [35] and Scanning micro X-ray diffraction [15][16][17][18][19][20][21]. Correlated spatial structural fluctuations in biological systems have been correlated with the emergence of quantum coherence in biological matter [35,41], in photosystems [42] and intrinsically disordered proteins [43,44], as well as in lamellar oxides showing quantum coherence [45][46][47][48], where non-Euclidean spatial geometries for signal transmission are able to emerge from a correlated disorder [22,48].…”
Section: Discussionmentioning
confidence: 99%
“…This makes standard experimental probes probing the average structure inadequate for the visualization of this heterogeneity, requiring highly spatially resolved probes. Biological tissues are typically intrinsically heterogeneous; indeed, nowadays new features and properties have been visualized using scanning methods with high spatial resolutions, such as by Atomic Force Microscopy [38][39][40], Confocal Microscopy [40], Scanning Electron Microscopy [35] and Scanning micro X-ray diffraction [15][16][17][18][19][20][21]. Correlated spatial structural fluctuations in biological systems have been correlated with the emergence of quantum coherence in biological matter [35,41], in photosystems [42] and intrinsically disordered proteins [43,44], as well as in lamellar oxides showing quantum coherence [45][46][47][48], where non-Euclidean spatial geometries for signal transmission are able to emerge from a correlated disorder [22,48].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the morphology of cells is of key importance for aging issues, deformability/elasticity analysis and diagnostic purposes. Thus, alterations of both mechanical and morphological properties in RBCs have been regarded as direct indicators of blood quality (4,5) and, for these reasons, are subject of intense and worldwide studies (6)(7)(8). The development of non-invasive methods that enable the identification of morphological and biomechanical variations of RBCs is thus of utmost scientific and medical interest.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been developed for investigating the difference of the mechanical properties of healthy and sick RBCs. Common techniques for addressing this purpose are based on particular microfluidic channels (10)(11)(12)(13), and on various electrical/optical techniques, such as atomic force microscopy (4,14), dielectrophoresis (15), and optical trapping techniques (16)(17)(18)(19)(20)(21). For example, parachute and slipper shapes are produced, respectively, in small and large one-dimensional microchannels (22), while opticallyinduced deformation using the optical stretcher is typically limited to cell elongation along a defined direction due to the applied antipodal stretching forces (19,23).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies using atomic force microscopy (AFM) directly examined the biomechanical properties of diabetic RBCs and demonstrated that they are less deformable than normal RBCs (Fig. 1), which could be due to the oxidation and glycosylation of hemoglobin and proteins on cell membrane under abnormal glycemic condition (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%